Esthetic crown lengthening for maxillary anterior teeth: an interdisciplinary case report - Ersan Çelik; Nehir Özden; Şule Tuğba Özak (Cumhuriyet Dental Journal, 2014)
Dentists are called on to provide restorations that are harmony with the lips, the face, the adjacent teeth, and a healthy periodontium. Periodontal theraphy plays an important role in the esthetic rehabilitation of the maxillary anterior segment, especially if the periodontal disease is present. This case report describes an interdisciplinary approach to the management of upper central incisors and application of Turkom-Cera all-ceramic fixed partial denture.Turkom-Cera all-ceramic fixed partial denture provides adequate aesthetics and function.